2014
DOI: 10.4314/ejesm.v7i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental concern, attitude towards green products and green purchase intentions of consumers in Lesotho

Abstract: Even though many people show high concern for the environment, the existing literature suggests a disjuncture between peoples' environmental concern and their shopping behaviours. Based on a survey of 200 shoppers around the precincts of two shopping malls in Lesotho, the objective of this paper is to examine the relationships among consumers' environmental concern, attitude towards green products, and green purchase intentions. Factor and regression analyses are mainly used to analyse data. The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
35
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 13 publications
10
35
0
7
Order By: Relevance
“…Environmental concern emerged as a major influence on product user SIC (H6a), stereotype negativity (H6b) and attitude H4b). The last of these findings is in line with those of Bamburg (2003) and others (see Khaola et al [2014] for details), although environmental concern was not significantly associated with EV product knowledge. It seems that high levels of environmental concern among the members of the sample who possessed this characteristic had not motivated a desire to acquire knowledge about EVs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Environmental concern emerged as a major influence on product user SIC (H6a), stereotype negativity (H6b) and attitude H4b). The last of these findings is in line with those of Bamburg (2003) and others (see Khaola et al [2014] for details), although environmental concern was not significantly associated with EV product knowledge. It seems that high levels of environmental concern among the members of the sample who possessed this characteristic had not motivated a desire to acquire knowledge about EVs.…”
Section: Resultssupporting
confidence: 90%
“…Intuitively, favourable attitudes towards a product should be associated with greater inclinations to purchase the product (Peter and Olsson, 2008), although attempts to demonstrate the presumed link between attitude and willingness to purchase have often been unsuccessful, especially in relation to environmental attitudes and actual environmental behaviour (for reviews of studies concerning this matter see for example Hini et al [1995]; Grewal et al [2000], Khaola et al [2014]). Hini et al (1995) noted the complexity of the attitude-willingness to purchase relationship and hence the many problems of measurement surrounding its estimation; given the large number of situational and personality factors that potentially affect a buying decision, e.g., variations in attitudes towards risk, the influences of marketing and advertising, prices of alternatives, and differences in the levels of importance that consumers attach to specific variables.…”
Section: Attitude and Willingness To Purchasementioning
confidence: 99%
“…These results are in accordance with several previous studies, namely Aman et al (2012), that there is an influence of environmental concern on attitudes in green product consumers in Sabahan, Malaysia. Khaola et al (2014) also found the same thing, that environmental concern had a positive relationship with attitudes towards consumers in the shopping center in Maseru-Lesotho.…”
Section: Discussionmentioning
confidence: 55%
“…Gupta and Denise (2009) state that there is a lot of inconclusive consumer research on the environment, where environmental concerns do not affect environmental attitudes and buying behavior of green products in the United States. Khaola et al (2014) also found the same thing, that environmental concern had a significant effect on attitudes towards consumers in the shopping center in Maseru-Lesotho. Based on the description above, the following hypothesis is proposed:…”
Section: Intention To Buymentioning
confidence: 53%
“…Fundamentally, moving towards a more sustainable transport system through the uptake of EVs is critically linked to the level of public awareness and concern about the environmental impacts of ICE vehicles as well as EVs. For instance, Khaola et al [65] investigated a possible correlation between people's concern for the environment and their attitudes towards green products (e.g., EVs) in general and found that there is a strong correlation between them. Additionally, Dogan and Ozmen [66] surveyed 752 respondents to investigate how the environmental concern would affect participants' attitudes towards buying EVs, and they discovered that participants with higher levels of environmental concern were more interested in EVs and more likely to purchase them.…”
Section: Shifting To Electric Vehiclesmentioning
confidence: 99%